Analyzing theoretical perspectives of shared governance model - Shah, Shakeela; Asimiran, Soaib; Lope Pihie, Zaidatol Akmaliah; Ahmad, Shamsuddin (International Institute for Science, Technology & Education, 2015)
The purpose of this paper is to explore the perspectives of shared governance as this university governance model is adopted by universities in the world involving all stake holders in the governance process specially faculty. Shared governance model is mostly hallmark in American colleges and universities which was promoted by AAUP (American Association of University Professors). Although, some researchers have pointed out its limitations but on the whole this model is successfully practiced in the academia.